DEVELOPING STUDENTS’ REFLECTION SKILLS THROUGH THE INTEGRATION OF PROBLEM-BASED LEARNING AND THE METHOD OF BUILDING ALGORITHMS - Syzdykova, G.; Zhampeissova, G.; Janabekova, S. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
This article describes how problem-based learning and algorithm design methods were integrated in action research and how effective this integration was in developing students’ reflective skills. Literature related to problem-based learning, as well as the method of creating algorithms and reflection skills, was studied and analyzed. During the observation of lessons, it was found that difficulties arose with fully describing the ways to solve tasks. The purpose of the study was to develop students’ reflection skills when solving a problem situation by creating algorithms for completing tasks. Research objectives: clarification of the research question; formation of a strategic plan; data collection; reflection; determination of new steps for the completed research. The study consisted of the following stages: study, analysis, selection of topics and educational goals in a calendar-thematic plan according to the eleventh grade curriculum; development of structured tasks; identifying solution steps; presentation and comparison of ready-made algorithms and evaluation tables; defining a joint solution; reflection and evaluation. The results of our previous study on identifying occupational dynamics were combined with this study. The study took into account the results of external summative assessment after the tenth grade, as well as the physiological, general and personal abilities, and practical abilities of students. The research process included four main cycles, including methods of problem-based learning and algorithm creation. Analyzing students’ written reflections after each round of inquiry helped determine next steps. In general, according to the results of the study, we were able to promote the formation of reflective skills in students and the development of design and research skills.